Opportunities for software reuse in an uncertain world: From past to emerging trends. Issue 8 (20th August 2019) - Capilla, Rafael; Gallina, Barbara; Cetina, Carlos; Favaro, John
Abstract: Much has been investigated about software reuse since the software crisis. The development of software reuse methods, implementation techniques, and cost models has resulted in a significant amount of research over years. Nevertheless, the increasing adoption of reuse techniques, many of them subsumed under higher level software engineering processes, and advanced programming techniques that ease the way to reuse software assets, have hidden somehow in the recent years new research trends on the practice of reuse and caused the disappearance of several reuse conferences. Also, new forms of reuse like open data and feature models have brought new opportunities for reuse beyond the traditional software components. From past to present, we summarize in this research the recent history of software reuse, and we report new research areas and forms of reuse according to current needs in industry and application domains, as well as promising research trends for the upcoming years.